Mesoproterozoic and Paleoproterozoic subcontinental lithospheric mantle domains beneath southern Patagonia: Isotopic evidence for its connection to Africa and Antarctica - Mundl, Andrea (2015)
New isotopic studies on mantle xenoliths from Santa Cruz Province, southern Patagonia, Argentina, reveal that at least three discrete subcontinental lithospheric mantle (SCLM) domains—the Deseado Massif, Tres Lagos, and Pali Aike—form the southernmost part of South America. Re-Os systematics yield early Paleoproterozoic (up to 2.5 Ga) SCLM formation ages (rhenium depletion ages, TRD) for Pali Aike spinel peridotites, while samples from the Deseado Massif and Tres Lagos indicate a younger SCLM origin with Neoproterozoic to Mesoproterozoic (0.9–1.3 Ga) and Mesoproterozoic to late Paleoproterozoic (1.3–1.9 Ga) TRD ages, respectively. Hf-Sr-Nd isotopic compositions indicate metasomatic overprinting of the majority of the samples, which, however, has not affected the Os isotopic system. Based on similar formation ages, the geological evolution of the Deseado Massif is most likely connected to the evolution of the Namaqua-Natal belt of South Africa. TRD ages from SCLM domains underneath Tres Lagos and Pali Aike indicate a common origin with crustal sections from Shackleton Range, Antarctica, positioning the southern tip of South America closer to west Antarctica in the reconstructed Rodinia supercontinent than previously assumed.